THE CONCEPT “FAMILY” IN THE RUSSIAN AND CHINESE LINGUOCULTURE: COGNITIVE, PHONOSEMANTIC AND EDUCATIONAL ASPECTS - Kolesnikova, Svetlana; Burskaya, Elena; Chibisova, istant (Revista Inclusiones, 2020)
Different languages possess such concepts which reveal the culture of a society, its traditions and their continuity in the modern world. The concept FAMILY is one of the most important values in education and upbringing. Such universals are reflected in all languages, their analysis and research are important for both comparative linguistics matter and the issues raised in a dialogue between cultures. The article analyzes the data obtained from the literature, folklore, and cinema, which represent the most complete picture of the functioning of the concept FAMILY; on the basis of the comparative analysis there have been identified similarities and differences of individual elements functioning as they representing the concept in question. The analyzed material reveals the relations between various aspects of this concept, their interaction and representation in both the language and the national view of the world. The article gives general information about the features of the concept FAMILY in the Russian and Chinese languages as well as the description of how this concept is represented in both cultures.